(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Tourism has become an integral part of the global economy and plays a significant role in the development of many countries. Uzbekistan possesses rich cultural and natural heritage which can be leveraged to promote tourism. This article aims to discuss the role of tourism in contributing to education and economic growth in Uzbekistan. It will analyze how tourism can help educate locals and foreigners about Uzbek culture and history. Additionally, it will examine how the tourism industry generates income and jobs for the Uzbek people.